A novel antibody-based enrichment and mass spectrometry approach for the detection of species-specific blood peptides in feed matrices. (April 2019) - Niedzwiecka, Alicia; Boucharef, Lyes; Hahn, Sarah; Zarske, Michael; Steinhilber, Andreas; Poetz, Oliver; Zagon, Jutta; Seidler, Tassilo; Braeuning, Albert; Lampen, Alfonso
Abstract: Blood is an important animal by-product and an attractive source for animal feed production. However, the outspread of bovine spongiform encephalopathy led to strict regulations on the usage of animal by-products in animal feed. Although, the ban on certain processed animal proteins has been partially abolished in recent years, it is still challenging to distinguish legal from illegal protein additives in complex feed products using analytical methods. To overcome these gaps, this study aimed to develop a tissue-specific and sensitive immuno-based enrichment and mass spectrometry-based detection method to identify haemoglobin peptides of ruminant or porcine origin when mixed in a background of vegetal feed, fish meal, aquaculture feed, blood compounds, or milk powder. Here we report the first analytical method able to species-specifically detect adulterations of as little as 0.05%–1% (w/w) ruminant blood meal in various matrices on a quadrupole-time of flight instrument. Highlights: Targets for species-specific blood product detection are presented. Immuno-enrichment of processed bovine and porcine haemoglobin is shown. A LOD of 0.05% (w/w) for bovine haemoglobin in vegetal feed is achieved. A protein extraction method is adapted for feed containing high amounts of fibre.